Early GnRH-agonist therapy does not negatively impact the endometrial repair process or live birth rate - Wang, Chen; Peng, Yangqin; Chen, Hui; Wang, Qinmei; Dong, Yu; Liu, Huimin; Yao, Yaoshan; Zhang, Shunji; Li, Yuan; Cai, Sufen; Li, Xihong; Lin, Ge; et al. (Frontiers in Endocrinology, 2024)
Study objective: To investigate whether different timings of GnRH-a downregulation affected assisted reproductive outcomes in infertile women with moderate-to-severe intrauterine adhesions (IUAs) accompanied by adenomyosis.Design: A retrospective case series.Setting: An assisted reproductive technology center.The study reviewed 123 infertile women with moderate-to-severe IUAs accompanied by adenomyosis undergoing their first frozen-thawed embryo transfer (FET) cycles between January 2019 and December 2021.The majority of patients had moderate IUA (n=116, 94.31%). The average Basal uterine volume was 73.58±36.50 cm 3 . The mean interval from operation to the first downregulation was 21.07±18.02 days (range, 1-79 days). The mean duration of hormone replacement therapy (HRT) was 16.93±6.29 days.The average endometrial thickness on the day before transfer was 10.83±1.75 mm. A total of 70 women achieved clinical pregnancy (56.91%). Perinatal outcomes included live birth (n=47, 67.14%), early miscarriage (n=18, 25.71%), and late miscarriage (n=5, 7.14%). The time interval between uterine operation and the first downregulation was not a significant variable affecting live birth. Maternal age was the only risk factor associated with live birth (OR: 0.89; 95% CI: 0.80-1.00; P=0.044).The earlier initiation of GnRH-a to suppress adenomyosis prior to endometrial preparation for frozen embryo transfer did not negatively impact repair of the endometrium after resection.